Cell-to-cell distances between tumor-infiltrating inflammatory cells have the potential to distinguish functionally active from suppressed inflammatory cells. (3rd May 2016) - Nagl, S.; Haas, M.; Lahmer, G.; Büttner-Herold, M.; Grabenbauer, G. G.; Fietkau, R.; Distel, L. V.
ABSTRACT: Beyond their mere presence, the distribution pattern of inflammatory cells is of special interest. Our hypothesis was that random distribution may be a clear indicator of being non-functional as a consequence of lack of interaction. Here, we have assessed the implication of cell-to-cell distances among inflammatory cells in anal squamous cell carcinoma and a possible association with survival data. Thirty-eight patients suffering from anal carcinoma were studied using tissue microarrays, double staining immunohistochemistry, whole slide scanning and image analysis software. Therapy consisted of concurrent radiochemotherapy. Numbers of stromal and intraepithelial tumor-infiltrating inflammatory cells (TIC) and the distances between cells were quantified. Double-staining of FoxP3 + cells with either CD8 +, CD1a + or CD20 + cells was performed. Measured cell-to-cell distances were compared to computer simulated cell-to-cell distances leading to the assumption of non-randomly distributed and therefore functional immune cells. Intraepithelial CD1a + and CD20 + cells were randomly distributed and therefore regarded as non-functional. In contrary, stromal CD20 + cells had a non-random distribution pattern. A non-random distance between CD20 + and FoxP3 + cells was associated with a clearly unfavorable outcome. Measured distances between FoxP3 + cells were distinctly shorter than expected and indicate a functional active state of the regulatory T cells (Treg). Analysis of cell-to-cell distances between TIC has the potential to distinguish between suppressed non-functional and functionally active inflammatory cells. We conclude that in this tumor model most of the CD1a + cells are non-functional as are the intraepithelial CD20 + cells, while stromal CD20 + cells and FoxP3 + cells are functional cells.